2018
DOI: 10.1002/jso.25044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of histological subtype on the prognosis of patients undergoing surgery for colon cancer

Abstract: MUC and SC are distinct subtypes of CC associated with a worse prognosis. These data can help inform discussion about prognosis and possibly direct adjuvant management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…The clinicopathological signi cance of a mucinous CRC subtype is well appreciated but remains controversial. Some studies have shown that MA has a worse prognosis than non-mucinous adenocarcinoma [23,[29][30][31], whereas others have shown no prognostic difference compared to conventional CRC [32,33]. Although there was no direct comparison with non-mucinous adenocarcinoma in the present study, compared with previous published data [11,34], the 5-year OS rate of this group (67.3%) of mucinous adenocarcinoma was lower.…”
Section: Discussioncontrasting
confidence: 87%
“…The clinicopathological signi cance of a mucinous CRC subtype is well appreciated but remains controversial. Some studies have shown that MA has a worse prognosis than non-mucinous adenocarcinoma [23,[29][30][31], whereas others have shown no prognostic difference compared to conventional CRC [32,33]. Although there was no direct comparison with non-mucinous adenocarcinoma in the present study, compared with previous published data [11,34], the 5-year OS rate of this group (67.3%) of mucinous adenocarcinoma was lower.…”
Section: Discussioncontrasting
confidence: 87%
“…The prognostic significance of presence of secretorymucin remains controversial. Some studies have reported poor prognosis with MC [12][13][14][15], whereas others failed to demonstrate the difference in survival outcomes between patients with MC and those with NMC [16,17]. A recent meta-analysis performed by Verhulst et al analyzed 44 studies and suggested that mucinous differentiation results in a 2-8% increased hazard of death after correction for stage.…”
Section: Discussionmentioning
confidence: 99%
“…Histological differences between mucinous and non-mucinous regarding prognosis are controversial. Some investigators suggested that mucinous carcinoma patients had a worse prognosis [42,43] while others did not [44,45]. Interestingly, we identified MC as being associated with the actual long-term survival.…”
Section: Discussionmentioning
confidence: 43%